Elaboración de licor destilado a base de uva Isabella y anís (Pimpinella Anisum L.) Con propiedades emulsionantes en combinación con agua (2025)
The global alcoholic beverage market has seen a significant transformation in recent decades, with a growing preference for innovative, light and visually appealing products. At a national level, Colombia is no stranger to this trend; young consumers are moving away from traditional drinks such as aguardiente, opting for more striking alternatives that include modifications in organoleptic properties such as color and texture. This change poses the challenge of creating products that respond to these new demands, taking advantage of native ingredients. To address this problem, an experiment was designed using Isabella grapes and anise, a raw material widely available in Colombia and recognized for its emulsifying properties. The methodology included the evaluation of key variables such as alcohol percentage, soluble solids content (Brix), refractive index, temperature and pH. These tests allowed the optimization of the formulation of a new beverage that would meet the expectations of the modern consumer.